Embodying the soul : medicine and religion in Carolingian Europe - Leja, Meg (Middle Ages series., 2022)
Embodying the Soul argues that classical medicine was reconfigured as a sacred Christian art across the Carolingian Empire in the ninth century, becoming not simply a method of physical rehabilitation but also a tool of spiritual transformation.